BIOREFINERY OF MICROALGAE: THE WORLD’S GREEN GEM FOR THE FUTURE SUSTAINABLE DEVELOPMENT - Angga Puja Asiandu; Widya Sari; Ahmad Saefun Naser; Wulan Rahmani Akmal; Dedy Setyawan; Dita Aulia Yulyanita (SEAMEO BIOTROP, 2025)
Article Highlights:- Integrated biorefinery provides economic and environmental benefits- Microalgae produce higher lipid content than plants- Generally, microalgae produce higher carbohydrate contents essential for bioethanol- Biohydrogen produced by microalgae is a future energy source- As a biofertilizer, microalgae promotes plant growth Abstract:Industrial and household activities leading to many pollutants have been reduced by the presence of microalgae in the phycoremediation. Microalgae transform pollutants into many forms of biorefinery, such as biofuel, biojet, bioethanol, biohydrogen, and biofertilizer. The chemical residue resulted from household and industrial activities has abundant elements (N, P, C) for microalgal cell growth. The contents of a microalgal cell, like lipid and carbohydrates, depend on the nutrition in the medium, the cultivation system, the microorganism-mediator, and the applied technology. Chlorella vulgaris, Botryococcus braunii, Spirulina platensis, Chlorella sp., Chlamydomonas sp., and Chlorococcum sp., are potential lipid-producing microalgae and are applied in biofuel and biojet. The carbohydrate of Cyanobacteria synechoccus sp., Nannochloropsis oculata, and Arthospira platensis is the main content to be utilized in bioethanol. Meanwhile, for the application of biohydrogen, H2 gas is converted from Scenedesmus obliquus fermentation. However, the process of bioethanol and biohydrogen needs bacteria as a mediator of fermentation. Spirulina and Scenedesmus are examples of microalgae supporting soil fertility as biofertilizers. Extraction of microalgae can increase growth promotors for plants, like amino acids, peptides, and proteins, and also antibacterial and antifungal. Optimizing excellent microalgae content in bioenergy will face several challenges, for example, imbalances of organic waste. However, the phycoremediation of microalgae is a sustainable and futuristic solution to fulfill the need for energy stock.